2019
DOI: 10.1002/lary.28320
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin and oropharyngeal pH monitoring to diagnose patients with laryngopharyngeal reflux

Abstract: Objectives The aim of this study was to compare the diagnostic accuracy of salivary pepsin with oropharyngeal pH monitoring using the Restech measurement system (Dx‐pH) for the diagnosis of laryngopharyngeal reflux (LPR). Study Design Prospective cohort study. Methods Seventy patients with primary symptoms related to LPR underwent gastroscopy, high‐resolution manometry, pH throughout 24‐hour monitoring (MII‐pH), and barium esophagography between October 2015 and May 2018. In addition, an ear, nose, and throat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 34 publications
3
54
1
1
Order By: Relevance
“…This is probably due to the close proximity of the monitor sensor to the oral pharynx/oral cavity, which is a short distance for the refluxate to travel from laryngopharynx to the oral cavity. Numerous investigations in adults have clearly demonstrated that salivary pepsin A associated with MII‐pH probe detected laryngopharyngeal reflux 21‐23 . The role of saliva pepsin A in diagnosing gastro‐oesophageal reflux needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably due to the close proximity of the monitor sensor to the oral pharynx/oral cavity, which is a short distance for the refluxate to travel from laryngopharynx to the oral cavity. Numerous investigations in adults have clearly demonstrated that salivary pepsin A associated with MII‐pH probe detected laryngopharyngeal reflux 21‐23 . The role of saliva pepsin A in diagnosing gastro‐oesophageal reflux needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigations in adults have clearly demonstrated that salivary pepsin A associated with MII-pH probe detected laryngopharyngeal reflux. [21][22][23] The role of saliva pepsin A in diagnosing gastro-oesophageal reflux needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies evaluated the diagnostic value of the Peptest compared to that of MII-pH or pH monitoring [6,14,15]. However, all those studies used the diagnostic criteria for GERD, not LPR.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that pepsin can be used as a reliable marker for the diagnosis of LPR; however, the accuracy, timing, and threshold values of pepsin test remain open questions [ 40 , 41 ]. Recently, a prospective study proposed a salivary pepsin cut-off value as an alternative tool for diagnosis of LPR [ 42 ]. The role of lacrimal pepsin test should be further investigated in a prospective study with a larger population of LPR patients included with the gold standard tests (pH throughout 24 h monitoring), in order to verify the role of pepsin as an additional tool for LPR diagnosis and its role in PROD syndrome.…”
Section: Discussionmentioning
confidence: 99%